Tren Politik Peringatan Darurat Garuda Pancasila Berlatar Belakang Biru di TikTok - Muna, Jazilatul; Dzikri, Irfa’i; Ramadhon, Laila Yusuf; Fatullah, Muhammad Rizky; Nisa , Pia Khoirotun (Universitas Pahlawan Tuanku Tambusai, 2025)
This study will analyze the phenomenon of social imitation triggered by viral content within the framework of mass communication sociology. The paper will discuss relevant theories, such as Bandura's social learning theory and the concept of social identity, to understand why individuals tend to imitate the behavior they see on social media. This study uses an interpretive paradigm that aims to understand the social meaning that arises from the phenomenon being studied, such as the viral content